(untitled) (The Review of Diabetic Studies, 2024)
The transition of care (TOC) from the high-acuity environment of the Emergency Department (ED) to the longitudinal setting of community-based primary care represents a critical juncture in the healthcare continuum, frequently characterized by fragmentation, information asymmetry, and elevated risk of adverse drug events (ADEs). As healthcare systems globally grapple with the dual imperatives of improving patient safety and containing costs, the standardization of referral processes has emerged as a priority policy objective. This narrative review comprehensively evaluates the role of The pharmacy team (Pharmacist and Pharmacist technician) s in harmonizing pharmacotherapy protocols between emergency physicians and General Practitioners (GPs)/Family Medicine providers. By synthesizing evidence from 35 peer-reviewed studies—including randomized controlled trials (RCTs), quasi-experimental designs, and economic evaluations published between 2002 and 2023—this report quantifies the impact of pharmacist-led interventions on hospital readmission rates, medication discrepancy prevalence, and health system expenditures. The analysis reveals that the integration of pharmacy team into the discharge pathway serves as a vital "semantic interoperability" layer, translating acute care interventions into sustainable community-based treatment plans. High-intensity interventions, characterized by a triad of medication reconciliation (MedRec), structured patient counseling, and post-discharge liaison, demonstrate a consistent ability to reduce 30-day all-cause readmissions by approximately 16% to 29% in high-risk geriatric populations. Furthermore, collaborative practice models where pharmacists draft or verify discharge summaries reduce clinically significant medication discrepancies in GP records by up to 50%. However, the efficacy of these interventions is heterogeneous, showing diminished returns in low-risk populations or when implemented as isolated touchpoints (e.g., telephonic outreach alone) without systemic integration. This report argues that the standardization of emergency-to-community referrals requires a fundamental shift from administrative handoffs to clinical harmonization. It proposes a risk-stratified framework wherein pharmacy team utilize standardized referral templates to explicate the rationale of medication changes, thereby empowering GPs to maintain continuity of care. The findings underscore the economic viability of such models, with targeted interventions yielding net savings through avoided utilization, despite the upfront costs of pharmacy staffing.